Modeling the Effect of the 2018 Revised ACGIH® Hand Activity Threshold Limit Value® (TLV) at Reducing Risk for Carpal Tunnel Syndrome. Issue 9 (2nd September 2019) - Yung, Marcus; Dale, Ann Marie; Kapellusch, Jay; Bao, Stephen; Harris-Adamson, Carisa; Meyers, Alysha R.; Hegmann, Kurt T.; Rempel, David; Evanoff, Bradley A.
Abstract: Recent studies have shown the 2001 American Conference of Governmental Industrial Hygienists (ACGIH ® ) Threshold Limit Value (TLV ® ) for Hand Activity was not sufficiently protective for workers at risk of carpal tunnel syndrome (CTS). These studies led to a revision of the TLV and Action Limit. This study compares the effect of applying the 2018 TLV vs. the 2001 TLV to predict incident CTS within a large occupational pooled cohort study (n = 4, 321 workers). Time from study enrollment to first occurrence of CTS was modeled using Cox proportional hazard regression. Adjusted and unadjusted hazard ratios for incident CTS were calculated using three exposure categories: below the Action Limit, between the Action Limit and TLV, and above the TLV. Workers exposed above the 2001 Action Limit demonstrated significant excess risk of carpal tunnel syndrome, while the 2018 TLV demonstrated significant excess risk only above the TLV. Of 186 total cases of CTS, 52 cases occurred among workers exposed above the 2001 TLV vs. 100 among those exposed above the 2018 value. Eliminating exposures above the 2001 TLV might have prevented 11.2% of all cases of CTS seen in our pooled cohort, vs. 25.1% of cases potentially prevented by keeping exposures below the 2018 value. The 2018 revision of the TLV better protects workers from CTS, a recognized occupational health indicator important to public health. A significant number of workers are currently exposed to forceful repetitive hand activity above these guidelines. Public health professionals should promulgate these new guidelines and encourage employers to reduce hand intensive exposures to prevent CTS and other musculoskeletal disorders.